Identification of Anti-Allergic Natural compounds through in-situ methods and Docking - Gupta, Ayushi (My University, 2024)
Over the past two decades, food allergies have become an increasing public health concern and need for efficacious anti-allergic agents. We searched for natural compounds that could antagonize the Aryl hydrocarbon receptor (AHR), a transcription factor involved in immune and allergic responses as potential anti-allergic agents. The vast literature review and data mining made possible the selection of 30 natural compounds in a thorough screening process. The AHR structure was obtained from the Protein Data Bank (PDB) and missing residues were incorporated using Swiss-Model to optimize its docking capacity. Sampling with molecular docking (AutoDock Vina) was performed and those having a binding affinity (>–6.0 kcal/mol), were selected for further theoretical/predictive analysis of selectivity as these may be considered suitable candidates to evaluate in cell cultures or animal KING etc. The molecular docking of high-affinity compounds with the AHR receptor, including detailed analysis on interaction types (hydrogen bond and hydrophobic contact) were validated using Discovery Studio. ADMET 2.0 Lab (online software) was then used to carry out ADMET analysis in order to examine drug-likeness of the shortlist compounds [16]. The Top Candidates: Beta Glucan, Alpha Tocopherol and Gama Tocopherol revealed ideal pharmacokinetic profiles with minimal toxicity.
Keywords: antiallary; natural antiallergic compounds; docking; protein Lig and Interaction